Green garbage substrates for growing geranium (Pelargonium spp.) in container - Acosta Durán Carlos Manuel; Acosta Peñaloza, Denisse (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the forest land is the main substrate used in the production of containerized ornamental plants, but its unlimited extraction causes a negative ecological impact. Among the alternatives for the replacement of the land of forest, are the garbage of gardening also called “green garbage”. There is a possibility that the inclusion of green waste as a substrate in the cultivation of containerized ornamental plants, have significant effects on the characteristics of growth and development of the same, so that the objective of this work was to characterize and determine the optimal dose for use as a substrate component for the production of containerized geranium. Physical chemistry laboratory analyzes were carried out and an agronomic evaluation experiment was carried out. Different proportions (100, 75, 50 and 25%) of green waste and scrubland were mixed, complemented with a general substrate (coconut fiber and sawdust, 50/50, v/v). A completely randomized design of eight treatments with eight repetitions was used. It was concluded based on the results that green waste has physicochemical characteristics similar to the land of the forest. In the growth and development of geranium in container, the results were statistically equal between the treatments of 100% of green waste and forest land in 16 variables studied. The green waste is a material that used as a substrate has the physicochemical characteristics necessary to successfully replace the land of forest in the cultivation of containerized geranium.